The Dynamics of the Students Asistensi Mengajar Program on Madrasah Ibtidaiyah in Malang Raya - Ali, Nur; Mukhlis, Sinthya Ziyadaturrahma; Kamila, Nayyifa Farah; Sa’idah, Anisa Wahdatus; Huda, Miftahul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The Educational Institutions and Teacher Training Institutions (Lembaga Pendidik dan Tenaga Kependidikan—LPTK) are perceived as lacking innovation in developing educational and teaching practices aimed at producing professional and character-driven teachers. It aligns with new findings indicating the lack of professionalism among teachers, as evidenced by violations of the teachers' code of ethics. Moral and ethical breaches are also frequently reported in schools. The leadership of LPTK has responded to this phenomenon by introducing programs that integrate and synergize teaching theories and practices, including implementing best practices, such as the Asistensi Mengajar (AM) program. This evaluative research examines the educational and teaching internships at Madrasah Ibtidaiyah across Malang Raya. It aims to enhance the quality of prospective teachers, ensuring they are professional and character-driven. Interviews, observations, and document analysis revealed that supervising teachers highly evaluate the competencies of AM students from the PGMI (Primary School Teacher Education) program at FITK UIN Malang. However, weaknesses remain in the area of developing teaching modules. School principals also provided positive assessments, noting that students generally exceeded expectations. Nonetheless, issues like lack of discipline in completing final assignments and adhering to school working hours were highlighted. Internal factors remain a significant obstacle. This study recommends that the management of the AM program conduct evaluations and introduce innovations in its management development.